Dimensions of artistic education: Experiences from a popular workshop of painting in a village of Seville. - Saavedra Macías, Francisco Javier; Rodríguez Gómez, Ana María (Arte, Individuo y Sociedad, 2008)
In the present paper is described the learning process of pupils of a popular workshop of painting. Discursive, behavioral and social aspects of learning are integrated. The need to analyze the concrete contexts of learning beyond the simple description of the activities inside the workshop is defended. The paper suggests the social origin of the discursive resources of the pupils and in this way “the artistic thought” is relabeled as “artistic speech”. The social contexts of activity out and inside the workshop are located in the apex of what is called an inverted triangle of the artistic education.